Perilaku ibu rumah tangga yang mempunyai balita dan sanitasi dasar rumah dengan kejadian diare pada balita - Retno Arienta Sari; Dyah Wulan Sumekar Rengganis Wardani; Ratna Dewi Puspita Sari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Mothers' personal and domestic hygiene and diarrhoea incidence in toddlers in Bandar Lampung, IndonesiaBackground: Diarrhea is still the second highest cause of child mortality in the world after pneumonia. Diarrhea is related to various factors. Maternal behavior and environmental sanitation are factors that are highly associated with the occurrence of diarrhea in infants.Purpose: To determine of the relationship between mother behavior and sanitation with the incident of diarrhea on toddlers in Kangkung Village Bumi Waras District Bandar Lampung City.Methods: This study was an observational analytic study with cross sectional approach, conducted in Kangkung Village, Bumi Waras District, Bandar Lampung City in October and November 2019. The sample were all toddlers and their mothers and taken with proportional random sampling technique. The research data were collected using the observation checklist method and questionnaire filling, then the data were analyzed using the chi square test.Results: Finding the proportion of diarrhea incidence was of 29.4% and without-diarrhea was of 70.6%. The results showed that the mother's hand washing behavior (p = 0.035), boiling drinking water (p = 0.036) and the availability of clean water (p = 0.049) were related to the incidence of diarrhea in toddlers. While the availability of feces disposal (p = 0.078), availability of waste disposal (p = 0.068) and waste water disposal facilities (p = 1,000) are not related to diarrhea.Conclusion: Obtaining several factors that are closely related to the incidence of diarrhea, with the behavior of the mother such as handwashing habits, provision of drinking water, and the availability of clean water that meets the requirements. While other factors such as the disposal of feces, garbage disposal, and waste water disposal, there have no relationship with the incidence of diarrhea among toddlers.Suggestion: The need for activities that involve the community from the family level, neighborhood groups to local government supported by the health department, health centers, schools with the aim of changing the behavior of community .Keywords: Mothers' Personal; Domestic Hygiene; Diarrhoea Incidence; ToddlersPendahuluan: Diare masih menjadi penyebab kematian balita tertinggi kedua di seluruh dunia setelah pneumonia. Penyakit diare berkaitan dengan berbagai faktor. Perilaku ibu dan sanitasi lingkungan menjadi faktor yang sangat terkait dengan kejadia diare pada balita.Tujuan: Mengetahui hubungan antara perilaku ibu dan sanitasi dengan kejadian diare pada balita di Kelurahan Kangkung, Kecamatan Bumi Waras, Kota Bandar Lampung.Metode: Penelitian analitik observasional dengan pendekatan cross sectional, dilakukan di Kelurahan Kangkung, Kecamatan Bumi Waras, Kota Bandar Lampung pada bulan Oktober dan November 2019. Sampelnya seluruh balita dan ibunya, diambil dengan Teknik proportional random sampling. Data penelitian dikumpulkan dengan metode checklist observasi dan pengisian lembar angket, kemudian dilakukan analisis data menggunakan uji chi kuadrat.Hasil: Didapatkan proporsi kejadian diare sebanyak 29,4% dan yang tidak diare 70,6%. Adapun hubungan faktor-faktor terkaitnya didapatkan; perilaku cuci tangan ibu (p = 0,035), memasak air minum (p= 0,036) dan ketersediaan air bersih (p= 0,049) berhubungan dengan kejadian diare pada balita. Sedangkan ketersediaan pembuangan tinja (p= 0,078), ketersediaan pembuangan sampah (p= 0,068) dan sarana pembuangan air limbah (p= 1,000) tidak berhubungan dengan diare.Simpulan: Didapatkan beberapa faktor yang berhubungan erat antara kejadian diare pada balita, dengan perilaku ibunya seperti kebiasaan cuci tangan, penyediaan air minum, dan ketersediaan air bersih yang memenuhi syarat. Sedangkan faktor lainnya seperti pembuangan tinja, pembuangan sampah, dan pembuangan air limbah, tidak didapatkan hubungan dengan kejadian diare pada balita.SARAN: Perlunya kegiatan yang melibatkan masyarakat dari tingkat keluarga, rukun tetangga sampai pemerintahan desa yang didukung oleh dinas kesehatan, puskesmas, sekolah dengan tujuan merubah perilaku PHBS masyarakat.